Female labour market outcomes and the impact of maternity leave policies - Hamish Low; Virginia Sánchez-Marcos (IZA Journal of Labor Economics, 2015)
This paper shows how family policies aimed at reconciling the pressures of family and work generate substantial variation in labour market outcomes across developed countries. We use a life-cycle model of female labour supply and savings behaviour, calibrated to the US economy, to assess the effect of introducing to the US a maternity leave policy similar to Scandinavian-type policies. We focus on the impact on gender differences in participation and in wages. We distinguish between the effect of the job protection offered by maternity leave and the effect of income replacement. Job protection leads to substantial increases in participation of mothers with children under 6, but with little long term effects. The effects on wages are minimal, with negative selection effects offsetting the reduced human capital depreciation. Income replacement has a limited impact on participation or wages.
Keywords: J13; J18; J22; 330; Labor supply; Maternal leave; Returns to work